BUNURILE CULTURALE – VICTIMELE FENOMENULUI TERORIST - Alexandra NICOLESCU (Intelligence și Cultura de Securitate)
Cultural heritage has the unique characteristic of transcending time, accompanying the rise and fall of civilizations. Access to cultural heritage is a human right, its destruction being a direct attack on the identity of a state and its population. Since the Arab Spring in the Middle East a series of acts of destruction, looting and illicit trafficking in cultural heritage items have taken place. This study aims to conduct an analysis on how the acts of destruction, robbery and illicit trade in cultural goods serve the Islamic State. In February 2015, the Islamic State distributed an online video in which the militants of the group destroy the ancient statues exhibited in the Mosul Museum. A first objective is to analyze the acts of destruction and looting of the museum in Mosul and to observe for what purpose they serve the terrorist group Islamic State. The video distributed on YouTube by the Islamic State generated an international reaction, being viewed with both horror and distrust. As a result, the international community has adopted legislation to regulate trafficking and illicit trade in antiques as a method of financing terrorism. The international community admits the causal link between crimes against cultural heritage and the financing of terrorism since 2015, following the media coverage of acts of destruction of artifacts and cultural heritage in the Middle East. This study looks at international legislation regulating the fight against the financing of terrorism through illicit trafficking and trade in cultural goods. The second objective focuses on the importance and necessity of protecting the cultural heritage against acts of destruction, looting and trafficking in order to obtain sources of income that are invested in terrorist activities. In this study, the research method focuses on the analysis of the international legislative framework and on the international scientific research that deals with the issues addressed. Actions to destroy the cultural heritage of the Middle East, especially in Syria and Iraq, have generated an international resurgence. Thus, the international community condemns the acts of destruction of the heritage, characterizing them as crimes against humanity and acts of cultural purification.